2007
DOI: 10.1158/0008-5472.can-06-4214
|View full text |Cite
|
Sign up to set email alerts
|

PC-1/PrLZ Contributes to Malignant Progression in Prostate Cancer

Abstract: PC-1/PrLZ gene overexpression has been identified to be associated with prostate cancer progression. Previous studies have revealed that PC-1 possesses transforming activity and confers malignant phenotypes to mouse NIH3T3 cells. However, the functional relevance of PC-1 expression changes during prostate cancer development and progression remains to be evaluated. In this study, gain-of-function and lossof-function analyses in LNCaP and C4-2 cells, respectively, were implemented. Experimental data showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 38 publications
(38 reference statements)
4
36
1
1
Order By: Relevance
“…Common phenotypes included smaller, rounder cells with reduced actin stress fibers, and we also noted significant positive correlations between in situ D52 or D53 and cyclin B1 expression (data not shown), as reported for endogenous D53 expression in MCF-7 cells, and exogenous D53 expression in MDA-MB-231-derived D53-H1 cells (32). Distinct phenotypes represented increased proliferation and anchorage-independent growth in D52-expressing cell lines only, in agreement with the findings of Lewis et al (28), where mouse D52 was expressed in 3T3 cells, and of previous studies where the D52 isoform PC-1/PrLZ was expressed in different cell types (26,29). A common limitation of the present and previous studies is the use of fibroblast cell lines, and analyses of D52 overexpression in a breast cell line such as MCF10A may be more informative in terms of the role of D52 role in breast cancer.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Common phenotypes included smaller, rounder cells with reduced actin stress fibers, and we also noted significant positive correlations between in situ D52 or D53 and cyclin B1 expression (data not shown), as reported for endogenous D53 expression in MCF-7 cells, and exogenous D53 expression in MDA-MB-231-derived D53-H1 cells (32). Distinct phenotypes represented increased proliferation and anchorage-independent growth in D52-expressing cell lines only, in agreement with the findings of Lewis et al (28), where mouse D52 was expressed in 3T3 cells, and of previous studies where the D52 isoform PC-1/PrLZ was expressed in different cell types (26,29). A common limitation of the present and previous studies is the use of fibroblast cell lines, and analyses of D52 overexpression in a breast cell line such as MCF10A may be more informative in terms of the role of D52 role in breast cancer.…”
Section: Discussionsupporting
confidence: 88%
“…Proliferation genes are emerging as a common driving force in prognostic cancer gene signatures (44). As D52 positively regulates cell proliferation and anchorage-independent growth (26,28,29), the reduced survival associated with high D52 expression in breast cancer likely reflects this contributing to a more proliferative and aggressive cancer phenotype. The identification of nonredundant cancer-promoting properties for D52 also support the specific targeting of D52 expression in cancer, as do the results of recent mapping studies indicating narrow gene amplification peaks at 81 Mb, corresponding to the position of the D52 locus (2 -5).…”
Section: Discussionmentioning
confidence: 99%
“…19 TPD52 promotes proliferation, migration/invasion, and metastasis in different cell models, 17,20,21 whereas knockdown of TPD52 induced apoptosis in breast and prostate cancer cell lines. 17,22 The underlying mechanisms are not yet fully understood, apart from the regulation of Akt/protein kinase B and Stat3/Bcl-2 signaling pathways shown in prostate cancer cell lines.…”
Section: Introductionmentioning
confidence: 98%
“…17,22 The underlying mechanisms are not yet fully understood, apart from the regulation of Akt/protein kinase B and Stat3/Bcl-2 signaling pathways shown in prostate cancer cell lines. 21,22 Studies have recently indicated a possible role of TPD52 in regulating DDR, where TPD52 levels positively correlated with G 2 chromosomal radiosensitivity in lymphocytes from women with or at risk of hereditary breast cancer. 23 A genome-wide association study combined with radiation cytotoxicity assays using human lymphoblastoid cell lines again identified TPD52 levels to be positively associated with radiation sensitivity, and TPD52 knockdown in multiple tumor cell lines significantly de-sensitized these cell lines to radiation treatment.…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Recent studies have demonstrated that TPD52 promotes metastasis; its expression increases with advancement of cancer and regulates apoptosis of cancer cells. 18,19 There was ample of interest given to TPD52 as an oncogene, due to its multifaceted functions in various cellular mechanisms and multiple carcinomas. 20,21 It is also proved that TPD52 increases lipid metabolism by facilitating de novo synthesis, exogenous uptake, and intracellular lipid storage.…”
Section: Introductionmentioning
confidence: 99%